Optic nerve involvement in patients with Lyme neuroborreliosis: an electrophysiological study - Szanyi, Jana; Kremlacek, Jan; Kubova, Zuzana; Kuba, Miroslav; Vit, Frantisek; Langrova, Jana; Gebousky, Pavel; Szanyi, Juraj (Documenta ophthalmologica, 2024)
PURPOSE: The aim of this neurophysiological study was to retrospectively analyze visual evoked potentials (VEPs) acquired during an examination for diagnosing optic nerve involvement in patients with Lyme neuroborreliosis (LNB). Attention was focused on LNB patients with peripheral facial palsy (PFP) and optic nerve involvement. METHODS: A total of 241 Czech patients were classified as having probable/definite LNB (193/48); of these, 57 were younger than 40 years, with a median age of 26.3 years, and 184 were older than 40 years, with a median age of 58.8 years. All patients underwent pattern-reversal (PVEP) and motion-onset (MVEP) VEP examinations. RESULTS: Abnormal VEP results were observed in 150/241 patients and were noted more often in patients over 40 years (p = 0.008). Muscle/joint problems and paresthesia were observed to be significantly more common in patients older than 40 years (p = 0.002, p = 0.030), in contrast to headache and decreased visual acuity, which were seen more often in patients younger than 40 years (p = 0.001, p = 0.033). Peripheral facial palsy was diagnosed in 26/241 LNB patients. Among patients with PFP, VEP peak times above the laboratory limit was observed in 22 (84.6%) individuals. Monitoring of patients with PFP and pathological VEP showed that the adjustment of visual system function occurred in half of the patients in one to more years, in contrast to faster recovery from peripheral facial palsy within months in most patients. CONCLUSION: In LNB patients, VEP helps to increase sensitivity of an early diagnostic process.
Keywords: Evoked Potentials, Visual; Young Adult; Male; zrakové evokované potenciály; zraková ostrost; retrospektivní studie; mladý dospělý; Adolescent; nemoci zrakového nervu; Child; dítě; Adult; Aged; dospělí; Lyme Neuroborreliosis; mužské pohlaví; senioři; nervus opticus; Visual Acuity; lymská neuroborelióza; mladiství; faciální paralýza; senioři nad 80 let; lidé; ženské pohlaví; Humans; Optic Nerve Diseases; Aged, 80 and over; Retrospective Studies; Facial Paralysis; Optic Nerve; Female; lidé středního věku; Middle Aged